Кардиоваскулярный риск у больных при аневризме брюшной части аорты - Никоненко, А. А.; Nikonenko, А. А.; Никоненко, Андрій Олександрович (My University, 2014)
Изучена частота кардиоваскулярных осложнений у больных при аневризме брюшной части аорты (АБЧА) на основе анализа данных их обследования с использованием электрокардиографии (ЭКГ), эхокардиоскопии, ультразвукового дуплексного сканирования (УЗДС). Признаки нарушения коронарного кровообращения по данным ЭКГ выявлены у 67,7% больных, гемодинамически значимое поражениех венечных артерий (ВА) — у 71,5%, поражение экстракраниальных артерий, требующее хирургической коррекции — у 38,3%. Своевременная оценка кардиоваскулярного риска дает возможность установить последовательность выполнения оперативных вмешательств, в частности, определить, какое из них осуществлять раньше — резекцию АБЧА либо операцию по устранению риска возникновения кардиоваскулярных осложнений. Frequency of cardiovascular pathology was studied in patients, suffering abdominal aorta aneurysm. For this purpose there was conducted analysis of data, concerning examination of patients, suffering abdominal aorta aneurysm: ECG, echo—CS, USDS, and of the CIM thickness. The signs of the coronary blood circulation disorders were revealed in accordance to ECG data in 67.7%, haemodynamically significant affections of coronary arteries were revealed in 71.5%, in 38.3% patients a pathology of extracranial arteries, needing surgical correction, was revealed. Timely estimation of cardiovascular risk gives possibility to determine the order of performance оf operations, what must be the first — resection of aneurysm or elimination of risk of the cardiovascular complications occurrence.
Cardiovascular risk in patients, suffering abdominal aorta aneurysm
Keywords: аневризма брюшной части аорты; кардиоваскулярный риск; комплексное обследование; аbdominal aorta aneurysm; cardiovascular risk; complex examination